CUSTOMER’S SERVICE EXPECTATION AND EXPERIENCE OF FREDDO COFFEE SHOP BANDUNG - Salsabila, Regina; Aprianingsih, Atik (Journal of Business and Management, 2018)
Abstract. The coffee industry has proliferated in big cities, especially the city of Bandung. The rapid development makes every coffee shop requires strategies to survive. One good marketing activity as a strategy that can be done to compete is by providing excellent quality service. Likewise, with Freddo Coffee Shop, they have experienced a decline in revenue for three consecutive months and want to get out of the problem by improving the quality of service and creating loyalty from customers. So, the purpose of this research is to evaluate the service quality of Freddo Coffee Shop by finding out the gap between customer’s service expectation and customer’s service experience.This study uses several attributes such as tangible, reliability, assurance, responsiveness, and empathy. The results of the measurements displayed through the Importance-Performance Matrix. Respondents of this study are 200 visitors of Freddo Coffee Shop and data were processed using SPSS. The result of this study is to give Freddo Coffee Shop recommendation to improve its service quality.Keyword: Customer’s Service Expectation, Customer’s Service Experience, Freddo Coffee Shop, Service Gaps, Service Quality